Abhydrolase domain containing 2, an androgen target gene, promotes prostate cancer cell proliferation and migration. (April 2016) - Obinata, Daisuke; Takada, Shogo; Takayama, Ken-ichi; Urano, Tomohiko; Ito, Akiko; Ashikari, Daisaku; Fujiwara, Kyoko; Yamada, Yuta; Murata, Taro; Kumagai, Jinpei; Fujimura, Tetsuya; Ikeda, Kazuhiro; et al.
Abstract: Background: The androgen receptor (AR) plays a key role in the development of prostate cancer. AR signalling mediates the expression of androgen-responsive genes, which are involved in prostate cancer development and progression. Our previous chromatin immunoprecipitation study showed that the region of abhydrolase domain containing 2 ( ABHD2 ) includes a functional androgen receptor binding site. In this study, we demonstrated that ABHD2 is a novel androgen-responsive gene that is overexpressed in human prostate cancer tissues. Methods: The expression levels of ABHD2 in androgen-sensitive cells were evaluated by quantitative reverse transcription polymerase chain reaction and western-blot analyses. LNCaP and VCaP cells with ABHD2 overexpression or short interfering RNA (siRNA) knockdown were used for functional analyses. ABHD2 expression was examined in clinical samples of prostate cancer by immunohistochemistry. Results: We showed that ABHD2 expression is increased by androgen in LNCaP and VCaP cells. This androgen-induced ABHD2 expression was diminished by bicalutamide. While stable expression of ABHD2 affected the enhancement of LNCaP cell proliferation and migration, siRNA-mediated ABHD2 knockdown suppressed cell proliferation and migration. In addition, the siRNA treatment significantly repressed the tumour growth derived from LNCaP cells in athymic mice. Immunohistochemical analysis of ABHD2 expression in tumour specimens showed a positive correlation of ABHD2 immunoreactivity with high Gleason score and pathological N stage. Moreover, patients with high immunoreactivity of ABHD2 showed low cancer-specific survival rates and a resistance to docetaxel-based chemotherapy. Conclusion: ABHD2 is a novel androgen-regulated gene that can promote prostate cancer growth and resistance to chemotherapy, and is a novel target for diagnosis and treatment of prostate cancer. Highlights: Abhydrolase domain containing 2 ( ABHD2 ) is a novel androgen-responsive gene. ABHD2 promotes cellular proliferation and migration. High ABHD2 expression is a poor prognostic factor for prostate cancer patients. ABHD2 could be a novel target gene for the treatment of prostate cancer.